PENGEMBANGAN KOGNITIF PADA PENDIDIKAN HOLISTIK DALAM PEMBELAJARAN AGAMA HINDU DI SD NO. 11 JIMBARAN KABUPATEN BADUNG - Ni Kadek Sinta Pratiwi (Jurnal Pendidikan Agama, 2023)
Cognitive is one of the areas of competence in holistic education that must be developed. Cognitive development can be developed through various lessons, one of which is Hindu religious learning. Cognitive development at SD No. 11 Jimbaran in Hindu learning has actually been carried out but there are still many things that need to be improved in the learning process and the methods used by teachers so that students are interested in learning. This is the background of the research entitled "Cognitive Development in Holistic Education in Hindu Learning at SD No. 11 Jimbaran, Badung Regency". This type of research uses qualitative research with an interpretive phenomenology approach. Data were collected by observation, interview, literature and document study techniques. Data analysis techniques with data reduction, data presentation, conclusion return. Based on data analysis, it was found (1) The cognitive development process in holistic education in Hindu learning at SD No. 11 Jimbaran is in accordance with the concept of holistic education, which is carried out through three aspects, namely the connectedness aspect, the openness aspect and the balance aspect. (2) The methods used as cognitive development solutions in holistic education in Hindu learning at SD No. 11 Jimbaran, Badung Regency are dharma carita, dharma gita, dharma kriya, dharma lila. (3) There are supporting and inhibiting factors for cognitive development in holistic education in Hindu religious learning at SD No. 11 Jimbaran, Badung Regency consisting of each internal factor and external factors.